(Re)create the internship in elementary school in pandemic times: the self-formative experiences of the pedagogy course of the Universidade Federal da Fronteira Sul – campus Erechim/RS (Revista Contexto & Educação, 2023)
This article presents a study that seeks to understand the formative experiences of students of the Pedagogy Degree course at the Universidade Federal da Fronteira Sul (UFFS) - Campus Erechim/RS, during the Curricular Internship in the Early Years of Elementary School, in the year 2020, at remote modality, due to the context of the Covid-19 pandemic. Thus, the research adopted a qualitative approach of a descriptive-interpretative character, developed based on the methodology of the research-formation of Josso (2004), made with a group of thirteen academics. Through the participants' narratives, two categories of analysis emerged: I) Autoformative experiences and teacher training; II) The role of the University in the formation of reflective praxis. Based on the interpretation of the data produced, the study revealed aspects of the reframing of the teaching profession and the formative experience from a remote internship, emphasizing the importance of self-formative processes, with a dialogic and reflective character, since the initial training, for the promotion of the critical thinking in the face of the pedagogical work of teaching in the early years of elementary school.
Keywords: Supervised internship; Pedagogy; Autoformative Processes; Covid-19 Pandemic